Digital follow-up and the perspective of patient-centered care in oncology: what’s the PROblem? - Giordano, Frank Anton; Welzel, Grit; Jahnke, Lennart; Ganslandt, Thomas; Wenz, Frederik (Oncology, 2020)
There is accumulating evidence from randomized trials suggesting that digital patient-centered care allows a more reliable detection of tumour-related symptoms and adverse events - with a direct impact on overall survival. Consequently, a variety of unsynchronized approaches were kicked off to (electronically) measure patient-reported outcomes (PROs). Despite increasing evidence that PRO data are highly relevant for patient care, the data generated in these initial projects lack standardized processing pathways in order to impact clinical routine; therefore, potential future routine PRO assessments require adequate analysis, storage and processing to allow a robust, reproducible and reliable incorporation into routine clinical decision-making. Here, we discuss relevant challenges of digital follow-up that need to be tackled to render PRO data as relevant to physicians as laboratory or biomarker data.
Published online December 05, 2018
Gesehen am 02.05.2019